Insectos asociados con flores de malezas del Jardín Botánico de Santiago de Cuba, con énfasis en Hymenoptera - Fernández T, José L; Garcés G., G; Portuondo F., E; Valdés T., P; Expósito E., I (Revista de Biología Tropical, 2001)
The insect visitors of flowers in nine weeds species were studied in the Botanical Garden of Santiago de Cuba, Eastern Cuba, during 1993 (March – June, spring season) and 1994 (January – March, end of winter and beginning of spring season). About 50 hours of collecting efforts were made at three times (0900-0930 hr in 1993; 0900-0930 hr, 1200-1230 hr and 1500-1530 hr in 1994). More than 140 species of at least 37 families were found; Hymenoptera dominated (with more than a half of specimens), followed by Diptera, Coleoptera and Lepidoptera. Among Hymenoptera, bees (Apoidea) were the largest group, especially Apis mellifera L; followed by wasps (Vespidae, Pompilidae, Sphecidae) and ichneumon flies (Ichneumonidae); Microhymenopterans were not sampled. Hymenopterans of each weed were compared for diversity, similarity, dominant and subdominant species, visitation time, sampling efficiency, etc. Each plant species had a particular Hymenoptera complex, almost one third of which were natural enemies of agricultural pests, and most are believed to be potential pollinators. Closely related species showed similar patterns of daily activity, with a peak at 0900 – 0930 hr for all plant species. Second grade polynomial equations were the best fitted models to describe the relationships between number of species and number of specimens, and between total number of species and number of samples (R2 = 0.9734 and R2 = 0.9573, p < 0.01). The role of weeds in the biodiversity of the agroecosystems is analyzed; as well as the effectiveness of this collection method to study Hymenoptera.